Fourier Single-Pixel Imaging Based on Lateral Inhibition for Low-Contrast Scenes - Kaiyu Zhang; Jie Cao; Fanghua Zhang; Yahui Jiang; Yang Cheng; Dong Wang; Qun Hao (IEEE Photonics Journal, 2019)
A Fourier single-pixel imaging technique based on lateral inhibition is proposed to improve the reconstruction contrast and quality for low-contrast scenes. The mathematical models are developed, and corresponding simulations and experiments are conducted to verify and evaluate the features. Results show that this strategy strengthens the image contrast and structural similarity index mainly under low sampling ratios compared with the traditional Fourier single-pixel imaging. It offers an optional solution for various Fourier single-pixel imaging applications at low sampling ratios for low-contrast scenes.